Fuzzy and neural control of an induction motor - Denai, Azzedine Mouloud; Attia, Sid Ahmed (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents some design approaches to hybrid control systems combining conventional control techniques with fuzzy logic and neural networks. Such a mixed implementation leads to a more effective control design with improved system performance and robustness.
Keywords: fuzzy control; neural networks; induction motor; vector control; speed observer